Case Report: Conservative Non-operative Management of a Neonate With Torted Wandering Spleen - Bourusly, Maha; Ayed, Mariam; Bahzad, Zainab (Frontiers in Pediatrics, 2022)
Background The management of wandering spleen (WS) with torsion, a rare pathological condition, is currently unclear. Most patients with this disorder are treated with surgical interventions, such as splenectomy or splenopexy. Case Presentation A newborn female presented with low hemoglobin (10.8 mg/L) and high total serum bilirubin (193 μmol/L) at 3 h of life. A palpable mass was observed during her physical examination, and a magnetic resonance imaging scan of the abdomen confirmed the presence of an infarcted WS with torsion. Upon conservative management with oral antibiotic prophylaxis, careful observation, and repeated follow-ups, the infant remained clinically stable. At 2 years of age, she had normal complete blood count, and a repeat technetium study revealed two splenunculi/splenules in the splenic bed. Conclusion Most patients with WS are treated surgically with splenectomy or splenopexy. Non-operative management may be a feasible treatment option in select cases with infarcted WS and may allow the natural process of autosplenectomy to occur.